A Shared Regulatory Element Controls the Initiation of Tcf7 Expression During Early T Cell and Innate Lymphoid Cell Developments - Harly, Christelle; Kenney, Devin; Wang, Yueqiang; Ding, Yi; Zhao, Yongge; Awasthi, Parirokh; Bhandoola, Avinash (Frontiers in Immunology, 2020)
1 Abstract The transcription factor TCF-1 (encoded by Tcf7) plays critical roles in several lineages of hematopoietic cells. In this study, we examined the molecular basis for Tcf7 regulation in T cells, innate lymphoid cells, and migratory conventional dendritic cells that we find express Tcf7. We identified a 1kb regulatory element crucial for the initiation of Tcf7 expression in T cells and innate lymphoid cells, but dispensable for Tcf7 expression in Tcf7-expressing dendritic cells. Within this region, we identified a Notch binding site important for the initiation of Tcf7 expression in T cells but not in innate lymphoid cells. Our work establishes that the same regulatory element is used by distinct transcriptional controllers to initiate Tcf7 expression in T cells and ILCs.